(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The article analyzes the problem of optimal liquidity management in commercial banks based on the integration of Basel III regulatory indicators such as the Liquidity Coverage Ratio (LCR) and the Net Stable Funding Ratio (NSFR), asset–liability management (ALM), internal funds transfer pricing (FTP), and liquidity stress testing. The proposed model envisages optimizing the portfolio of liquid assets and the funding structure under constraints while maintaining the balance between bank profitability and safety. Publicly available data on Uzbekistan’s banking system indicate that LCR and NSFR exceed the minimum requirement (100%), which implies the presence of liquidity buffers; however, optimization is necessary because excess liquidity entails an “opportunity cost” (foregone profit).